Exploring electronic, optoelectronic, and thermoelectric properties of ternary compound MgSrSe2 from first-principles study - Qian Wang (AIP Advances, 2020)
The electronic, optoelectronic, and thermoelectric properties of a ternary structure MgSrSe2 are investigated using density functional theory. MgSrSe2 is found to be a direct bandgap semiconductor with a bandgap of 2.04 eV. The photon energy calculated results show that the absorption spectra are in UV-A light, and MgSrSe2 could be applied for a photodetector. Optoelectronic properties, such as the dielectric function, absorption coefficient, reflectivity, refractive index, extinction coefficient, and energy-loss of MgSrSe2, are systematically discussed. The effective mass of the band edge curvature analysis indicates that the p-type MgSrSe2 is suitable for the thermoelectric material, and the maximum dimensionless figure of merit value can be up to 1.33 at 800 K. The results show that MgSrSe2 is a potential optoelectronic and thermoelectric material, and encourage further experimental works for its synthesis.